Occupational lung cancer risk among men in the Netherlands. Issue 4 (10th October 2007) - Preller, L; Balder, H F; Tielemans, E; van den Brandt, P A; Goldbohm, R A
Abstract : Objectives: To assess male lung cancer risks for industrial sectors in the Netherlands and to estimate the proportion of lung cancer attributed to working in specific industrial sectors. Methods: Associations were studied among men aged 55–69 years (n = 58 279) from the prospective Netherlands Cohort Study. 1920 incident lung cancer cases were available after 11.3 years of follow-up. Based on a case-cohort design, and using Cox proportional hazards models, risks were estimated for blue collar workers in 26 industrial sectors. Results: Adjustment for individual smoking habits affected risk estimates for some sectors, but adjustment for fruit/vegetables and alcohol intake did not. Adjusted for confounders, an increased risk of lung cancer was observed for employment for ⩾15 years in blue collar jobs in the "electronics and optical instruments" industry (rate ratio (RR) 1.99; 95% CI 1.18 to 3.35), "construction and homebuilding business" (RR 1.64; 95% CI 1.21 to 2.22) and "railway company" (RR 2.40; 95% CI 1.00 to 5.73). The attributable fraction for working for ⩾15 years in these three industries was 5%. In three other sectors there was a statistically non-significant elevated RR of >1.5. Conclusions: Male lung cancer risk is increased in several industrial sectors. Approximately 2000 lung cancer cases between 1986 and 1997 in the 55–69-year-old age group in the Netherlands may be attributable to working for ⩾15 years in the three sectors with increased risk. In addition, estimates for occupational lung cancer risks for sectors may be biased if no individual information is available on smoking habits.